Impact of dietary Alpinia Katsumadai extracts on production performance, meat quality, and gene expression in AMPK signaling regulatory pathway of Wuzhishan pigs - Wu, Hongzhi; Yu, Xilong; Zhang, Xiaoyu; Ipemba, Euphrème; Bakala, Ghislain Boungou; Leveut, Lessebe Gambou Dieu; Peng, Weiqi; Ji, Fengjie; Li, Hanfeng; Cao, Ting; Lv, Renlong (Frontiers in Veterinary Science, 2025)
Pork is one of the most consumed meats globally, especially in China, Europe, and North America. Meat quality is a multifaceted concept that can be assessed from several key perspectives, such as palatability, nutritional value, and processing characteristics. This study investigated the effects of dietary Alpinia Katsumadai extracts on meat quality, amino acids, and long-chain fatty acids profiles, as well as gene expressions in the AMPK signaling regulatory pathway of Wuzhishan pigs. Forty-eight pigs were selected and randomly divided into four groups, with six replicates and two pigs for each replicate. The control group (CON) was administered a basal diet, while the experimental groups received basal diets supplemented with 400, 600, and 800 mg/kg of Alpinia Katsumadai extracts, respectively (designated as AK1, AK2, and AK3). The results showed that compared with the control group, the components of the treated groups exhibited significant differences. Specifically, the muscle inosinic acid, intramuscular fat, and triacylglycerol contents were higher (p < 0.05). In terms of quality, the b* and L* values of the longissimus dorsi muscle at 45 min post-slaughter were higher (p < 0.05), and drip loss was lower (p < 0.05). Regarding metabolism, the muscle C14:0, C16:0, C18:3 n3, C18:2 n6c, C20:4 n6, and PUFA proportions were higher (p < 0.05), while MUFA proportions were lower (p < 0.05). Additionally, the relative expressions of ACC, PRKAA1, PRKAG1, and MyHC I in the muscle were higher (p < 0.05), whereas those of PRKAB1, PRKAB2, PPARγ, and MyHC IIb were lower (p < 0.05). In the liver, the relative expressions of ACC, PRKAA1, and PRKAG1 were higher (p < 0.05), and those of PPARγ, PRKAB1, PRKAB2, and PGC-1α were lower (p < 0.05). These findings indicate that Alpinia Katsumadai extracts enhance the meat composition, quality, amino acids, long-chain fatty acids, and gene expressions in the AMPK signaling regulatory pathway of Wuzhishan pigs. The optimal dosage identified in this study is 600 mg/kg.